(untitled) (Journal of Pharmaceutical Negative Results, 2023)
It is witnessed that the marketplace of mutual funds is complex and contain high visibility of risks. Considering this, investors’ decision regarding mutual fund investment is critical. Therefore, the study aims to evaluate the implications of knowledge and information sharing facets along with involvement of financial advisers and behavioural aspects. The primary qualitative method has been adopted which has implemented the semi-structured interview. In the interview process, three participants have been selected to gain adequate data related to the topic. Since it is a qualitative study, therefore, a thematic analysis has been presented. The results showcased that investor’s perception and attitude is determined through gaining accurate information as well as investment advisers have an influential impact. It is concluded with the observation that both information sharing and financial experts are responsible to induce changes in investor perception. Beside, the involvement of behavioural aspects also alters the dimensions of decision-making.